1990
DOI: 10.1210/jcem-70-2-491
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Hyperthyiroidism: Studies on Platelet Counts, Mean Platelet Volume, 111-Indium-Labeled Platelet Kinetics, and Platelet-Associated Immunoglobulins G and M*

Abstract: We compared in 15 patients with hyperthyroidism (11 with Graves' disease, 3 with toxic adenoma, and 1 with multinodular goiter) platelet counts (PC) and mean platelet volume (MPV) before and 3 weeks after initiation of antithyroid drug therapy when the patients were euthyroid. In addition, platelet kinetic studies of autologous 111-indium-labeled platelets and platelet-associated immunoglobulins G and M (PAIgG and PAIgM, respectively) were investigated. The control group for the platelet kinetic studies consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
2
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
5
47
2
2
Order By: Relevance
“…These associations are regarded, nowadays, as autoimmune polyglandular syndrome (APS; types 1–3) [7], characterized by the association between endocrine and nonendocrine autoimmune disease, either during the clinical or the subclinical phase. Several morphological and functional changes in platelets have been described in patients with thyroid disorders [8, 9]. Isolated or familial autoimmune idiopathic thrombocytopenia (AITP) has been described in patients with Graves’ disease (GD) in the presence of platelet-associated IgG (paIgG) [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These associations are regarded, nowadays, as autoimmune polyglandular syndrome (APS; types 1–3) [7], characterized by the association between endocrine and nonendocrine autoimmune disease, either during the clinical or the subclinical phase. Several morphological and functional changes in platelets have been described in patients with thyroid disorders [8, 9]. Isolated or familial autoimmune idiopathic thrombocytopenia (AITP) has been described in patients with Graves’ disease (GD) in the presence of platelet-associated IgG (paIgG) [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated or familial autoimmune idiopathic thrombocytopenia (AITP) has been described in patients with Graves’ disease (GD) in the presence of platelet-associated IgG (paIgG) [10, 11]. However, paIgG has been reported both in GD and Hashimoto’s thyroiditis (HT) also in the absence of AITP [8, 11]. Unfortunately, the criteria used in these studies were not homogeneous and based mainly on the thyroid function; indeed, the routine diagnostic use of antiperoxidase antibodies [3, 12]has apparently led to an increase, over the last few years, in the diagnoses of AITD, whilst still in an early, subclinical phase [1, 3, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperthyroid patients are prone to developing thromboembolism, bleeding due to various coagulation defects are also reported [11][12][13]. Increased levels of a specific fragment of fibrinogen, which is degraded by plasmin, suggest hyperfibrinolysis in hyperthyroid patients [14].…”
mentioning
confidence: 99%
“…Panzer et al reported the presence of antiplatelet IgG in patients with Grave's as well as improved platelet counts and increased mean platelet volume after successful antithyroid therapy. 8 In addition to the coexistence of thyroidstimulating immunoglobulins (TSIs) and antiplatelet antibodies as a potential mechanism for Grave's-associated thrombocytopenia, some have postulated that in Grave's patients, TSIs and other thyroid antibodies might actually bind to the platelets themselves. The postulated site for binding would be a truncated actin-binding protein on the platelets that would link the high-affinity Fc receptor of immunoglobulin G to the platelets' cytoskeleton, thereby accelerating their destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition and treatment of the hyperthyroid state with antithyroid medications can lead to significant improvement in the platelet count. 1,8 We report this rare but critical clinical relationship.…”
mentioning
confidence: 87%